A Comparative Study of Performances between Manufacturing Cooperatives and Manufacturing Private Firms - Kiani, Ahmad; Jafarzadeh, Saeed; Koohestani, Hossein; Eineddin, Reza Arfaei (Journal of Asian Business Strategy, 2015)
Cooperative sector is a new form of economic activities which emerge a new generation of people taking advantage of legitimate and balanced ownership by using public potentials and facilities and sharing benefits of their work. The present study compares performances of manufacturing cooperatives and manufacturing private firms in Bostan Abad, Iran. The methodology used for current study is a descriptive survey. Data gathering instrument was an author-developed questionnaire which was used after determining its validity and reliability. Results from testing studied hypotheses indicate that mutual trust and satisfaction are higher among workers of cooperatives than private firms (99%) are. There is also a significant difference between incomes of cooperative and private workers. Responsibility as well as participation in decisions is higher within cooperatives than private firms (99%) are. In general, it can be concluded that social aspects are stronger in terms of selected indices in cooperatives than private firms and demands of workers and members are more and better satisfied in cooperatives than private firms.